Pengaruh Pemberian Ampas Kopi Terhadap Pertumbuhan dan Hasil tanaman Caisim (Brassica chinensis L.) Pada tanah Spodosol: The Effect Of Giving Coffee Grounds On Growth And Yield Of Caisim Plants (Brassica Chinensis L.) In Spodosol Soil - undut, Saurdot Pakpahan; Sulistiyanto, Yustinus; Sinaga, Soaloon; Sirenden, Ruben Tinting; Amelia, Vera (Fakultas Pertanian Universitas Palangka Raya, 2023)
The purpose of this study was to determine the real effect of coffee grounds on the growth and yield of caisim (Brassica chinensis L.) and to determine the appropriate dose of coffee grounds to increase the growth and maximum yield of caisim (Brassica chinensis L.). This research was conducted from April 2022 to May 2022 at the Peat Techno Park (PTP) University of Palangka Raya. This study used an environmental design, namely Completely Randomized Design (CRD) with 5 treatments and 4 replications. The treatments were Control (P0), 20 g (P1), 40 g (P2), 60 g (P3), 80 (P4). The parameters used in this study were plant height, number of leaves, year width, crown weight and root weight. From the observations obtained, it was analyzed to determine the real effect of the treatment using analysis of variance (F test) at the level of α = 5% and 1%. Data analysis will be continued with the Least Significant Difference Test (LSD) at α = 5% to determine the significant difference between treatment levels. The treatment of coffee grounds significantly affected the height, number of leaves, leaf area, top crown weight and root weight of caisim plants. Giving 20 g of coffee grounds gave optimum results on the growth and yield of caisim plants.